EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) TERHADAP HASIL BELAJAR MATEMATIKA - Dafid Slamet Setiana (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2020)
The aim of this study was to find out that cooperative learning model type Student Teams Achievement Division (STAD) was more effective than the direct learning model toward learning outcomes in mathematic. Type of research was quasi-experimental. The sampling technique was done by using cluster random sampling technique. Data collection techniques performed with documentation and test techniques. Research instruments included test of validity, level of difficulty, discrimination power, and reliability. T-test was used to analyze the data. After doing the research, the researcher found that the average score of experimental class was higher than the control class. It represented through description of mathematics learning outcomes scores. T-test showed that the STAD type cooperative learning model was more effective than the direct learning model toward learning outcomes in mathematics. Keyword: effectiveness, student teams achievement division (STAD), learning outcomes, mathematics